2019
DOI: 10.1016/j.cell.2019.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Coordination of Chromatin Torsional Mechanics and Topoisomerase Activity

Abstract: Highlights d A single chromatin substrate is torsionally softer than a braided substrate d Thus, DNA supercoiling should primarily partition to the front of a replisome d Yeast topo II shows a strong preference for a single chromatin substrate d Thus, torsional mechanics and topoisomerase activity coordinate synergistically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 98 publications
(136 reference statements)
6
95
0
Order By: Relevance
“…As for the possibilities to use DNA fibers to test our hypothesis, it was recently demonstrated that a single chromatin fiber is torsionally softer than a braided one by direct torque measurements. 64 Since SMF directly interferes with torsional mechanics of DNA, experiments with DNA fibers will not help to test our hypothesis. Moreover, in a single oriented molecule experiment, there are no reasons for DNA rotation and replication under intrinsic forces because it is not a living system.…”
Section: Discussionmentioning
confidence: 99%
“…As for the possibilities to use DNA fibers to test our hypothesis, it was recently demonstrated that a single chromatin fiber is torsionally softer than a braided one by direct torque measurements. 64 Since SMF directly interferes with torsional mechanics of DNA, experiments with DNA fibers will not help to test our hypothesis. Moreover, in a single oriented molecule experiment, there are no reasons for DNA rotation and replication under intrinsic forces because it is not a living system.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that in csm3Δ, tof1Δ, and tof1-ΔC strains topoisomerases I and II do eventually relieve torsional stress in front of the fork (either independently or as part of multiprotein complexes), but perhaps only after the torsion has reached higher levels. Of note, Top2 was recently shown in vitro to strongly favor a single chromatin fiber over two independent fibers as a substrate (Le et al 2019), a preference that would support its general activity ahead of the fork irrespective of replisome composition. Our findings indicate that either Top1 or Top2 is able to impose replication fork pausing at the Fob1-RFB, through a mechanism that we dub "sTOP" ("slowing down with topoisomerase I and II") ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it remains unclear how Top2 is recruited to the replisome, for example through as yet unknown protein-protein interactions or DNA topology. Recruitment of Top2 ahead of the fork may be favored by its biophysical preference for a single parental chromatid (Le et al, 2019).…”
Section: Dna Topology Topoisomerases and Replisome Pausingmentioning
confidence: 99%